Infant perception and cognition recent advances, emerging theories, and future directions - Oakes, Lisa M., 1963- (New York ; Oxford : Oxford University Press, 2011)
The cognitive revolution in the 1950s and 1960s led researchers to view the human mind--like a computer--as an information-processing system that encodes, represents, and stores information and is constrained by limits on hardware (the brain) and software (learning strategies and rules).
Description based on print version record.
Includes bibliographical references and index.
Keywords: Perception in infants; Cognition in infants